Comparison of the microalgal community within fast ice at two sites along the Ross Sea coast, Antarctica - Ryan, KG; Hegseth, EN; Martin, AR; Davy, SK; O'Toole, R; Ralph, PJ; McMinn, A; Thorn, CJ (Antarctic Science, 2006)
Diverse microbial communities survive within the sea ice matrix and are integral to the energy base of the Southern Ocean. Here we describe initial findings of a four season survey (between 1999-2004) of community structure and biomass of microalgae within the sea ice and in the underlying water column at Cape Evans and Cape Hallett, in the Ross Sea, Antarctica as part of the Latitudinal Gradient Project. At Cape Evans, bottom-ice chlorophyll a levels ranged from 4.4 to 173 mg Chl a m -2 . Dominant species were Nitzschia stellata , N. lecointei , and Entomoneis kjellmanii , while the proportion of Berkeleya adeliensis increased steadily during spring. Despite being obtained later in the season, the Cape Hallett data show considerably lower standing stocks of chlorophyll ranging from 0.11 to 36.8 mg Chl a m -2 . This difference was attributed to a strong current, which may have ablated much of the bottom ice biomass and provided biomass to the water below. This loss of algae from the bottom of the ice may explain why the ice community contributed only 2% of the standing stock in the total water column. Dominant species at Cape Hallett were Nitzschia stellata , Fragilariopsis curta and Cylindrotheca closterium . The low biomass at Cape Hallett and the prevalence of smaller-celled diatoms in the bottom ice community indicate that the ice here is more typical of pack ice than fast ice. Further data will allow us to quantify and model the extent to which ice-driven dynamics control the structure and function of the sea ice ecosystem and to assess its resilience to changing sea ice conditions.